Ourspace: the efficacy of a group dynamics-based social support application in increasing cohesion and physical activity - Kurz, Daniel L. (Kansas State University, 2015)
Background: Emerging technologies (i.e. smartphones, Internet) may be effective tools for promoting physical activity (PA); however few studies have provided effective means of using them to enhance social support. Face-to-face programs that use group dynamics-based (GDB) principles of behavior change have been shown to be highly effective in promoting group cohesion and PA however few studies have examined their effects in web-based programs. The present study examines the effect of a GDB application on group cohesion and PA. We expected partner’s level of presence to moderate this effect. Methods: Subjects (n=135) were randomized into same-sex dyads and randomized to an experimental condition: low cohesion/low presence (LC-LP), high cohesion/low presence (HC-LP), high cohesion/high presence (HC-HP), or individual. Participants performed two blocks of planking exercises (pre-post). Between blocks, participants in partnered conditions were met their partner using either a standard social support application (LC-LP) or a GDB social support application (HC-LP and HC-HP), where they participated in a series of team-building exercises. Individual subjects were given a rest period. Participants in the HC-HP saw a live video stream of their partner exercising during Block 2. Perception of cohesion was measured using a modified Physical Activity Group Environment-Questionnaire (PAGE-Q). PA was calculated as performance during Block 2 controlled for by performance during Block 1. Results: Findings show that perception of cohesion was higher for the HC-LP condition compared to the LC-LP conditions in three of the four cohesion dimensions: ATG-S(p=0.002), GI-T(p=0.002), GI-S(p=0.022), but not ATG-T(p=0.170). Cohesion means did not differ between HC-LP and HC-HP conditions. Only the HC-HP condition produced significant gains in PA compared to other conditions (HC-LP: p=0.044; LC-LP: p=0.018; Individual: p=0.001). Conclusions: Findings suggest that a GDB application may be an effective method of improving group cohesion, however it may be insufficient on its own to improve PA. Increasing presence may be an effective method of improving performance during a single session of PA, however further research is needed to determine its effect on long term behavior change.
Keywords: Physical Activity; Social support; mHealth; Cohesion; Internet; Behavioral Sciences (0602); Public Health (0573)